APOBEC3G Polymorphisms and Implications for a Population with Chronic Hepatitis B Virus in Burkina Faso - Compaore, Tegwinde Rebeca; Ouattara, Abdoul Karim; Sawadogo, Isidore; Traore, Lassina; Sagna, Tani; Djigma, Florencia Wendkuuni; Ouedraogo, Henri Gautier; Simpore, Jacques (International Journal of Microbiology, 2023)
Host factors such as APOBEC3G were associated with hypermutation, which might interfere with HBV replication. The need to assess the impact of APOBEC3G polymorphisms on a hepatitis B-infected population is highlighted by a previous study. Thus, our study aimed to characterize two APOBEC3G single nucleotide polymorphisms and evaluate their association among chronic carriers of hepatitis B in Burkina Faso. Three hundred forty-five (345) individuals were recruited, including 106 HBsAg positive and 239 HBsAg negative. APOBEC3G polymorphisms rs6001417 and rs8177832 DNA genotyping were characterized by TaqMan allelic discrimination. The minor allele G of rs600417 frequency was higher among participants with chronic hepatitis B. Furthermore, rs600417 was associated with the dominant model p<0.05. Multivariate analysis for chronic hepatitis B risk factors shows that the risk of chronic hepatitis B for genotype CG and GG of rs6001417 seem to be significantly reduced and are, respectively, OR = 0.25 (95% CI 0.09–0.72, p≤0.01) and OR = 0.08 (95% CI 0.02–0.31, p≤0.001). In the analysis, the GG genotype of rs8177832 seems to increase the risk of chronic hepatitis B by more than six (6) times, and it was statistically significant OR = 6.41(95% CI 1.74–23.55, p≤0.01). This study shows that APOBEC3G may be a susceptibility gene for chronic hepatitis B virus carriage in our context. The locus could contribute to the mediation of host native resistance to HBV infection.